Menanamkan Jiwa Kewirausahaan Peserta Didik di Sekolah Islam - Rozi, Bahru (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2023)
Economic problems are problems that arise when wants and needs exceed available resources. People who have unlimited wants and needs, while the available resources cannot meet these needs, then economic problems arise from there. The objectives of this research are (1) to find out the objectives of entrepreneurship learning for students (2) to find out the components of entrepreneurship learning for students. This research uses library research methods. The results of this research show: (1) the aim of entrepreneurship learning is to provide provisions for students and instill attitudes, values and a spirit of independence as well as the ability to collaborate and embed the entrepreneurial paradigm or mindset in students. (2) The curriculum components must include education (educational, creativity, multiple intelligence), types of work/occupation (occupation, vocational subject matter) and entrepreneurship/entrepreneurship.